2015
DOI: 10.3945/jn.115.221283
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically Healthy Obesity Is Not Associated with Food Intake in White or Black Men

Abstract: Healthy obesity in men is not associated with a healthier diet. Future studies need to consider dietary patterns, which may better inform the holistic effect of diet on healthy obesity, in prospective analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Nevertheless, differences in MHO prevalence according to ethnicity have been reported, although this recent meta-analysis did not include any studies based on African cohorts [ 33 ]. There are reports indicating that overall dietary intake was not associated with healthy obesity in both Europeans and African Americans [ 27 , 34 ]. In addition to lifestyle and ethnicity, data was not available on the pharmacological compounds included in the ART regimens of the participants as well as the duration of treatment with those compounds, precluding detailed analyses by potency of pharmacological compounds and duration of treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, differences in MHO prevalence according to ethnicity have been reported, although this recent meta-analysis did not include any studies based on African cohorts [ 33 ]. There are reports indicating that overall dietary intake was not associated with healthy obesity in both Europeans and African Americans [ 27 , 34 ]. In addition to lifestyle and ethnicity, data was not available on the pharmacological compounds included in the ART regimens of the participants as well as the duration of treatment with those compounds, precluding detailed analyses by potency of pharmacological compounds and duration of treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, MHO was defined as having ≤2 of the following five metabolic syndrome components: high systolic and diastolic blood pressures, high plasma TG concentration, low HDL-C concentration, high fasting blood glucose, and a large waist circumference; or ≤1 abnormal component excluding waist circumference (4). Additional criteria, including high plasma total cholesterol, LDL-cholesterol, and C-reactive protein concentrations, 2-hour blood glucose concentrations during an oral glucose tolerance test, and indices of insulin sensitivity/resistance (based on the homeostasis model assessment of insulin resistance [HOMA-IR] , have also been used to determine MHO (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). In some studies, even people with impaired glucose tolerance, T2D, and history of CVD were considered metabolically healthy because they did not have a sufficient number of the specified metabolic abnormalities to be identified as MUO (15,(25)(26)(27)(28).…”
Section: Definition Of Metabolically Healthy Obesitymentioning
confidence: 99%
“…The prevalence of MHO, defined as "normal" insulin sensitivity (based on the HOMA-IR score) and absence of any metabolic syndrome components (excluding waist circumference), is approximately 7%, whereas half of all people with obesity can be classified as MHO when defined as ≤2 metabolic syndrome components (including waist circumference). However, it is likely that these results overestimate the prevalence of MHO in the general population, because many studies excluded people with existing cardiometabolic diseases, such as T2D and CVD (9,11,13,28,(42)(43)(44).…”
Section: Definition Of Metabolically Healthy Obesitymentioning
confidence: 99%
“…One variable that has been scrutinized as a possible determinant of MUO is diet. Although some large population studies have identified subtle differences in diet as a determinant of the MUO phenotype,6, 7 others have not been able to detect a difference in either calorie or nutrient consumption between MHO and MUO subgroups 8, 9, 10. This may be due to the imperfect quality of dietary data in population studies, which in general rely on self-report and recall.…”
mentioning
confidence: 99%